2024
DOI: 10.1038/s41598-024-57154-3
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in kynurenine pathway metabolites in young women with autoimmune thyroiditis

Anna Krupa,
Agnieszka Łebkowska,
Marcin Kondraciuk
et al.

Abstract: The kynurenine pathway (KP) of tryptophan degradation includes several compounds that reveal immunomodulatory properties. The present study aimed to investigate the alteration in KP metabolites in young women with autoimmune thyroiditis (AIT) and their associations with thyroid function. The thyroid function tests, antithyroid antibodies measurement and ultrasonography of the thyroid gland have been performed in 57 young women with AIT and 38 age-matched healthy controls. The serum levels of tryptophan, kynure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Upon immune stimulation, the so called ‘kynurenine switch’ snaps into action, and most Trp molecules enter immunocompetent cells and are metabolized therein via the kynurenine pathway ( 47 ). Kynurenine binds to the aryl hydrocarbon receptor (AHR) in multiple immune cell types, leading to immune regulation ( 19 , 48 ). It has been shown that after immune stimulation, immune cells generate high levels of various intracellular Trp metabolites ( 49 ), which in turn is involved in the induction of the synthesis of cytoskeletal proteins and regulation of immune cell motility ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Upon immune stimulation, the so called ‘kynurenine switch’ snaps into action, and most Trp molecules enter immunocompetent cells and are metabolized therein via the kynurenine pathway ( 47 ). Kynurenine binds to the aryl hydrocarbon receptor (AHR) in multiple immune cell types, leading to immune regulation ( 19 , 48 ). It has been shown that after immune stimulation, immune cells generate high levels of various intracellular Trp metabolites ( 49 ), which in turn is involved in the induction of the synthesis of cytoskeletal proteins and regulation of immune cell motility ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that after immune stimulation, immune cells generate high levels of various intracellular Trp metabolites ( 49 ), which in turn is involved in the induction of the synthesis of cytoskeletal proteins and regulation of immune cell motility ( 50 ). Indoleamine 2,3-dioxygenase 1 (IDO1), the key enzyme of kynurenine pathway, is one of the major regulators of the function of immune cells, controlling the balance between stimulation and suppression of the immune system at sites of local inflammation and thus is relevant to a wide range of autoimmune and inflammatory diseases ( 19 ). Significant attention has been paid to the immunoregulatory role of IDO1 in the most prevalent, organ-specific autoimmune endocrinopathies such as T1D and AIT ( 19 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations